Digital Era Challenges and Opportunities of Artificial Intelligence in E-Government and E-Business - Rubiyo Rubiyo (Jurnal Penelitian Pendidikan, 2024)
The development of the digital era encourages emergence intelligence artificial intelligence (AI) that has open a very big opportunity in improvement e-government and e- business services . In the sector government , intelligence artificial can push improve efficient service to the community with provide automation and analyzing data as well ability taking decision based on data. Services based on this data Not yet covers to throughout the region so that Still need development infrastructure technology that can reach throughout remote parts of Indonesia. Research This use approach studies literature , the author also identified and collected data from various article that examines about digital, AI, E-government and e- business , challenges and opportunities , strengthening infrastructure is also very important For guard personal data security . Author conclude that data security is also one condition For increase sector business that takes advantage of intelligence artificial for safety customer can maximum . Marketing strategy can utilise intelligence artificial with automation its operation so that marketing more effective . even though adoption intelligence artificial Still Lots obstacles , and not yet profitable perpetrator business small medium (SME) thing This happen Because difficulty access technology intelligence artificial . Challenge intelligence artificial , e-government and e- business Policy institutions procurement goods / services government (LKPP) can give solution profitable for SMEs.